Efficacy of Selected Insecticide Seed Treatments on Bird Cherry-Oat Aphids in Wheat - Erckert, Kathryn; Davis, Holly; Whitworth, Jeff (My University, 2018)
Bird Cherry-Oat Aphids, Rhopalosiphumpadi (Linnaeus) (BCOA) are common in Kansas wheat fields and may vector Barley Yellow Dwarf Virus, causing awidevariety of problems including stunted and non-reproductive wheat (Whitworth and Ahmad, 2008). This experiment consisted of an experimental seed treatment and compared it to a control and a seed treatment already commercially available.Results showed that although the experimental treatment didn't provide control; seeds with CruiserMaxx® seed treatment were protected until 22 days after planting.The results indicate that the aphids these common seed treatments are fighting against were not as effective as previously determined.
Keywords: Fall 2018